Adaptation strategies against growing environmental and social vulnerabilities in mountain areas - Jodha, Narpat S (Himalayan Journal of Sciences, 2007)
This paper deals with the strategies adopted by the Hindu Kush Himalayan (HK-H) mountain communities in response to adverse natural and human induced circumstances. The quality of life and growth options in mountains (including hills) are deeply rooted in mountain specificities (e.g., fragility, marginality, diversity). Hence, the disregard of these mountain specificities while using mountain resources reduces communities’ options and makes them more vulnerable to environmental and economic distresses. The paper first introduces the concept of vulnerability and the traditional low-intensity system of resource use. It then deals with the decline of such traditional systems due to the intensification of resource use caused by the integration of the relatively isolated mountain areas into mainstream economies. The paper concludes with a call for introduction of macro level policies to: (i) Minimize the vulnerability potential of globalization and global environmental change and (ii) Enhance local capacities to withstand and adapt to the changes promoted by these global processes. This discussion covers larger part of the present paper.Himalayan Journal of Sciences 3(5) 2005 p.33-42